Female education and its impact on fertility - Jungho Kim (IZA World of Labor, 2023)
The negative correlation between women's education and fertility has been observed across regions and time, although it is now weaker among high-income countries. Women's education level could affect fertility through its impact on women's health and their physical capacity to give birth, children's health, the number of children desired, and women's ability to control birth and knowledge of different birth control methods. Each of these mechanisms depends on the individual, institutional, and country circumstances experienced. Their relative importance may change along a country's economic development process.
Keywords: J13; J18; J22; I26; O15; 330; female education; fertility; demand for children; fertility control costs; returns to education; family planning